Kedudukan Perkawinan Beda Agama Yang Telah Di Catatkan Ditinjau Dari Undang-Undang Nomor 1 Tahun 1974 Dan Kompilasi Hukum Islam - Annisa Nailis Saadah; Sahruddin Sahruddin; M. Yazid Fathoni (Private Law, 2023)
This study aims to analyze the position of registered interfaith marriages in terms of Law Number 1 of 1974 and the Compilation of Islamic Law. The type of this research is normative legal research. Then the approach used is a statutory, conceptual, and an analytical approach. Sources of legal materials are obtained from existing legal materials, which are legislations and court decisions. Based on the results of the research, the position of interfaith marriage that has been registered in terms of Law Number 1 of 1974 and the Compilation of Islamic Law is illegitimate because it does not meet the provisions of Article 2 paragraph (1) of the Marriage Law as a criterion for the validity of marriage. The interfaith marriage has consequences on (1) the status and position of the child, which is illegitimate, (2) the religious status of the child is the responsibility of both parents, (3) non-Muslim heirs are entitled to inheritance property given through mandatory wills, (4) joint property of interfaith marriages is divided based on the consent of husband and wife, and (5) the breakup of interfaith marriages is carried out by filing a marriage annulment application through the district court.